Lymphatic research in the human spleen unveils a differentiated splenic sinusoid - Karvinen, Leo (My University, 2024)
Keeping the human body in a healthy condition requires a flawless cooperation between myriads of physiological systems, the lymphatic system being one of them. While most often considered to be responsible for immune cell trafficking and mobilization of leukocytes during immune responses, the lymphatic system plays also a vital role in lipid trafficking from the intestines and preventing lymphedema by absorbing interstitial fluids leaking out of the capillaries of the circulatory system. To effectively fulfil these tasks, the lymphatic system is comprised of multiple organs and long vessels all over the human body, all complete with complicated pathways to achieve its functions. For us to study further how the lymphatic system works, we need a solid understanding regarding the organization, structure and the pathways of the lymphatic system. While much is known about the lymphatic system and multiple breakthrough medications have been developed due to this knowledge, there are still a lot of enigmatic components we do not know much about especially regarding the functionality or even the organisation of the lymphatic vasculature. One of these enigmatic components is the human spleen. Throughout history, many researchers have tried to conclude the existence or absence of lymphatic vessels in the human spleen. After reviewing available literature, it was concluded that very little is known about the human splenic microanatomy regarding lymphatic vasculature or cell trafficking. In this work, we will review the currently available literature of the human splenic microanatomy in the context of immunity and conduct experiments using novel and commonly used lymphatic endothelial markers to further investigate the state of lymphatic vasculature in the human spleen.
Keywords: Lymphatics, Lymphatic endothelium, Spleen, CLEC4G, CLEC4M